2002
DOI: 10.1002/1521-3951(200201)229:2<935::aid-pssb935>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

500-560 nm Laser Emission from Quaternary CdZnSSe Quantum Wells

Abstract: ZnSe-based laser diodes with emission wavelength from 500 to 560 nm are studied. The long wavelength operation of these laser diodes requires careful optimization of the CdZnSSe quantum well material. It is shown that under stoichiometric growth conditions quantum wells with high optical and structural qualtity can be realized. Employed in laser structures room-temperature cwoperation around 560 nm is obtained. In comparison with laser diodes emitting at 505 nm it is found that the high Cd content of the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Chalcogenide glass fibers transmit in IR region. These glasses are used for fabricating active devices, such as infrared transmitting optical fiber, optical amplifiers, infrared lasers, blue laser diodes and efficient femto second switches [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide glass fibers transmit in IR region. These glasses are used for fabricating active devices, such as infrared transmitting optical fiber, optical amplifiers, infrared lasers, blue laser diodes and efficient femto second switches [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting emission wavelength was 560 nm. Further details can be found in [6,7]. For processing ridge structures out of the QD lasers the top layers were etched down beneath the 10 µm injection stripe by ion beam etching about 1 µm into the middle of the p-side waveguide layer.…”
Section: Resultsmentioning
confidence: 99%
“…The n-side layers and the QW were doped with chlorine as well as the p-side layers were doped with nitrogen-plasma. Further details of growth can be found in [6]. For strain compensation, the QW has to be embedded into tensile strain layers.…”
Section: Quantum Well Laser Diodes / Strain Compensating Layersmentioning
confidence: 99%
“…In the literature, there are a few reports about CdZnSSe. Most of them are related to using in ZnSe-based laser diodes [19,20]. Only Chavhan et al [21] reported the growth and characterization of CdZn(S 1−x Se x ) 2 alloy film using the solution growth technique and in our previous study [22], it was reported the optical properties of * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%